Role of the B-cell receptor in chronic lymphocytic leukemia: where do we stand? - Fais, Franco; Bruno, Silvia; Ghiotto, Fabio (Italian Journal of Anatomy and Embryology, 2010)
The past 15 years have witnessed an enormous effort in studying B-cell Chronic Lymphocytic Leukemia. A great number of researches brought significant novel information and a better understanding of the natural history of this disease. This mini review will focus on the studies related to the Immunoglobulin variable (IgV) genes rearrangements that compose the B-cell receptor (BcR) of the leukemic clones. These stud ies have defined a role for the antigen(s) in the paths that lead to leukemic clone generation/expansion and underscore the informative value represented by BcR analyses.